Determination of fatty acids in Allium tuncelianum (Tunceli garlic) by gas chromatography with flame ionization detection (GC–FID). Issue 3 (23rd September 2021) - Ugur, Yilmaz; Karaaslan-Ayhan, Nagihan; Icen, M. Sina; Bicim, Tulin; Erdogan, Selim; Yaman, Mehmet
Abstract: Garlic has an important place in daily nutrition. It is consumed by people because of its antimicrobial, antibacterial, and antioxidant properties, and it is also known to be good for many diseases. Along with these properties of garlic, its fatty acid content is also important. The goal of this study is to determine the fatty acids in Allium tuncelianum (Tunceli garlic), which grows naturally in Tunceli, Turkey, by gas chromatography with flame ionization detection (GC–FID). Fifteen of 37 fatty acids studied were detected in Allium tuncelianum, and the primary fatty acids in the sample extracts were determined to be the polyunsaturated fatty acid (PUFA) linoleic acid (C18:2n6c, 41.595%) and the monounsaturated fatty acid (MUFA) oleic acid (C18:1n9c, 33.302%). Small quantities of saturated fatty acids (SAFAs) were also present, including palmitic acid (C16:0, 11.739%), henoicosanoic acid (C21:0, 6.946%), and stearic acid (C18:0, 2.362%).